2004
DOI: 10.1021/ja045749e
|View full text |Cite
|
Sign up to set email alerts
|

Polytheonamides A and B, Highly Cytotoxic, Linear Polypeptides with Unprecedented Structural Features, from the Marine Sponge,Theonellaswinhoei

Abstract: Polytheonamides A and B are highly cytotoxic polypeptides with 48 amino acid residues isolated from the marine sponge, Theonella swinhoei. The structure of polytheonamide B was determined by spectral and chemical methods, especially extensive 2D NMR experiments, which resulted in the unprecedented polypeptide structure; the N-terminal glycine blocked with a 5,5-dimethyl-2-oxo-hexanoyl group, the presence of eight tert-leucine, three beta-hydroxyvaline, six gamma-N-methylasparagine, two gamma-N-methyl-beta-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
119
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(126 citation statements)
references
References 47 publications
(38 reference statements)
1
119
0
4
Order By: Relevance
“…[117] . [120,121] wahrscheinlich durch posttranslationale C-Methylierung von Valinseitenketten am b-Kohlenstoff über einen radikalischen, SAMvermittelten Transfer von CH 3 C-Gruppen gebildet (Schema 8 B). Eine analoge C-Methylierung einer Ile-Seitenkette zur entsprechend verzweigten Seitenkette kommt ebenfalls vor.…”
Section: Nichtproteinogene Aminosäurenunclassified
“…[117] . [120,121] wahrscheinlich durch posttranslationale C-Methylierung von Valinseitenketten am b-Kohlenstoff über einen radikalischen, SAMvermittelten Transfer von CH 3 C-Gruppen gebildet (Schema 8 B). Eine analoge C-Methylierung einer Ile-Seitenkette zur entsprechend verzweigten Seitenkette kommt ebenfalls vor.…”
Section: Nichtproteinogene Aminosäurenunclassified
“…Intriguingly, the sequence has alternating d-and l-amino acid residues, except for the eight glycine units. [2] These unique structural features enable 1 to fold into a distinctive three-dimensional structure not found in ribosomal proteins. Extensive NMR and modeling experiments by Hamada …”
mentioning
confidence: 99%
“…Overall, compound 10 exhibited H + -channel activity analogous to that of 1 except for its weak voltage dependency. Most importantly, it was found that the hydrophobic N-terminal region Ncap- [1][2][3][4][5][6][7][8][9][10][11], which is responsible for the significant difference in the cytotoxicity of 1 and 10, is not an essential component for channel formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Die Polytheonamide A und B sind die wahrscheinlich größten und strukturell komplexesten bekannten nicht-ribosomalen Peptide. [2] Sie wurden aus dem marinen Schwamm Theonella swinhoei isoliert, in dem sie möglicherweise von einem noch unbekannten symbiotischen Mikroorganismus produziert werden. Sie bestehen aus 48 Aminosäuren und einer N-terminalen 5,5-Dimethyl-2-oxohexanoyl-Einheit (Abbildung 1).…”
unclassified